Health‐related quality of life in adolescents with cerebral palsy; a cross‐sectional and longitudinal population‐based study. (6th September 2022) - Larsen, Selma Mujezinović; Terjesen, Terje; Jahnsen, Reidun B.; Diseth, Trond H.; Ramstad, Kjersti
Abstract: Aims: The aims of this population‐based cross‐sectional and longitudinal study were to investigate different aspects of health‐related quality of life (HRQoL) in adolescents with cerebral palsy (CP), to define possible changes in HRQoL from childhood to adolescence and to identify factors associated with low HRQoL in adolescence. Methods: Proxy‐reports of 64 adolescents, aged 12–17 years, with bilateral CP in GMFCS levels III‐V participating in a surveillance programme, included five of the six domains from the HRQoL instrument Caregiver Priorities & Child Health Index of Life with Disabilities (CPCHILD): (1) Activities of Daily Living and Personal Care, (2) Positioning, Transfer and Mobility, (3) Comfort and Emotions, (5) General Health and (6) Overall Quality of Life, and the two questions on pain from the Child Health Questionnaire (CHQ). Fifty‐eight participants comprised the longitudinal sample. Results: From childhood to adolescence, the mean CPCHILD domain scores decreased slightly in General Health and remained unchanged in the other four domains. In the domain General Health, the number of medications increased, which was the reason for the score decrease. Pain severity increased significantly. Severe motor impairment was associated with low scores in domains 1, 2, 3 and 5, and more severe pain with low scores in domains 2, 3, 5 and 6 . A low domain score in childhood was associated with a low score in each corresponding domain in adolescence. Interpretation: An assessment of HRQoL should be included in CP surveillance programmes because this could identify needs for interventions in individuals with severe CP. This study indicates the importance of improved pain management in both children and adolescents with severe CP.